2020
DOI: 10.1021/acsnano.0c04512
|View full text |Cite
|
Sign up to set email alerts
|

Anderson Localization Enabled Spectrally Stable Deep-Ultraviolet Laser Based on Metallic Nanoparticle Decorated AlGaN Multiple Quantum Wells

Abstract: Random lasers exhibit many exotic properties, including chaotic behavior, light localization, broad angular emission, and cost-effective fabrication, which enable them to attract both scientific and industrial interests. However, before the realization of their potential applications, several challenges still remain including the underlying mechanism and controllability due to their inherent multidirectional and chaotic fluctuations. Through more than two decades of collaborative efforts, the discovery of Ande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…We investigated Anderson localization to clarify the relationship between SERS and light scattering. Light scattering is inherent in many nanostructured materials and holds promise for new approaches to light management in optical devices, such as random lasers, disordered photonic waveguides, and plasmonic devices. In particular, disordered NR materials have optical properties with significant reflectivity arising from multiple light scattering, which have been observed on dielectric semiconductor NRs such as Si and GaP. , Light scattering contributes significantly when the optical wavelength becomes shorter and comparable to the diameter of the NRs. Generally, the small-scatter (Rayleigh) limit is valid for diameters d ≪ l /(π n ) and when the critical diameter is set well below l /10, where l is the wavelength .…”
Section: Resultsmentioning
confidence: 99%
“…We investigated Anderson localization to clarify the relationship between SERS and light scattering. Light scattering is inherent in many nanostructured materials and holds promise for new approaches to light management in optical devices, such as random lasers, disordered photonic waveguides, and plasmonic devices. In particular, disordered NR materials have optical properties with significant reflectivity arising from multiple light scattering, which have been observed on dielectric semiconductor NRs such as Si and GaP. , Light scattering contributes significantly when the optical wavelength becomes shorter and comparable to the diameter of the NRs. Generally, the small-scatter (Rayleigh) limit is valid for diameters d ≪ l /(π n ) and when the critical diameter is set well below l /10, where l is the wavelength .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, no direct correlation was found between the Au's typical absorption plasmonic peaks (~ 500–600 nm) and the material's PTs' activity. This observation could be attributed to the heat generated by light scattering in particles located close to each other, promoting the heating through the Anderson Localization mechanism [ 57 , 58 ]. Indeed, small and more dispersed AuMu@pH9 particles synthesized in all concentrations exhibit weaker PT properties than the coral-shaped AuMu@pH6 particles and the crystalline AuMu@pH3 ones (Additional file 1 : Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…When irradiated, the energy is transformed into heat and can be used for various applications, including hyperthermia treatments [ 55 , 56 ]. The major mechanism of this phenomenon is the PT due to absorbance at the plasmonic resonance, which can be tuned by means of the size of the AuNP[ 57 ]. However, it was shown that even the off-resonance PT effect could be present in such a system which may be originated from light localization effects [ 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…For a more detailed analysis of the random lasing, the power Fourier transformation (PFT) of the spectrum was performed to calculate the effective cavity length, as shown in Figure S10. The spatial dimensions could be obtained from the formula of the Fourier component, P m = mnL c /π, where m is the order of the Fourier harmonic, n is the gain medium refraction index (1.34), and L c is the cavity length. According to the relation of the Fourier peaks and the statistical distribution of the cavity length (inset of Figure S10), the effective optical cavity length was calculated to be 18.86 μm. This revealed that there exist 2D close-loop resonance paths by comparing the cavity length and the thickness of the device.…”
Section: Resultsmentioning
confidence: 99%